IMPLEMENTATION OF THE ELECTRE METHOD IN THE RECOMMENDATION SYSTEM AND API SERVICE PROVISION FOR TOURIST DESTINATIONS IN BANYUMAS REGENCY WITH INTERACTIVE MAPPING - Guntur Satya Pramudya; Permadi, Ipung; Chasanah, Nur (Jurnal Teknik Informatika (Jutif), 2024)
The Banyumas Regency is a region with a diverse range of tourist attractions, making tourism one of its crucial economic sectors. The multitude of tourist destinations in Banyumas often poses a challenge for visitors in choosing destinations that align with their preferences. To address this issue, this research applies the Elimination et Choix Traduisant la Réalité (ELECTRE) method in multi-criteria decision-making. The objective of this study is to provide recommendations for suitable tourist destinations based on tourists' interests, along with an interactive mapping feature that offers a geographical overview and distance information for these destinations. Recognizing the importance of accessible tourism information, this research also implements Application Programming Interface (API) services to facilitate the integration of tourist destination data into various applications and platforms. The system is built as a web-based application using the Laravel framework and MySQL database. The output of this research is a web-based recommendation system that can be used to help tourists who want to vacation according to their preferences and the API service helps interested parties to integrate tourism data into their system.